Lublin in journal „Tygodnik ilustrowany” in time period 1859 – 1939 - Janus, Krzysztof; Janusz, Renata (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
The paper presents the descriptions and relations of Lublin city life which were found in the back numbers of Tygodnik Ilustowany from years 1859- 1939. Representations include information about important for the city and its habitants events. Attached drawings show the city’s and people’s appearance, living conditions and lifestyle? in this period.